Optimization of bow and arrow design subject to aerodynamic characteristics - Mohammad Azizi, Mohammad Khairul Fadhli; Mohd Saleh, Siti Juita Mastura; Mohanad Al-Ghriybah, Mohanad Al-Ghriybah (FAZ Publishing, 2019)
Archery is a type of sport that has been practiced for centuries all around the globe whether it is used as war weapon, for hunting animals or just for sport competition. The aim of this research is to come up with the optimization of bow and arrow design subject to aerodynamic characteristics. In order to do that, the stiffness of the bowstring of different material was investigated while the stiffness of different arrow shaft material was analysed. Next, the optimal arrow fletcher shape was developed. Throughout this research, only one bow was used for all shots plus the string material analysis was conducted on one bow only. The design variable for fletcher optimization was set on the type of material, dimension, and fletcher orientation based on aerodynamics performance. Due to time constrain, only three type of shaft material was analysed and the data collection was in the form of arrow speed. The speed of the arrows was measured by using a chronograph. A consistency test also conducted in order to see the hit pattern of the arrow at three different ranges. Interviews with top Malaysian archer in both traditional and modern discipline were conducted to investigate their equipment choices. Parabolic shape has higher speed compared to shield shape. Offset orientation causes the arrow to have tighter group compared to straight orientation. Feather fletcher that is lighter than plastic fletcher produces much faster arrow. Fast Flight string material outrun other string material by produces fastest arrow speed. The aluminium shaft is the fastest based on the experiment but archers prefer carbon due to their physical strength and consistent spine rating.